Perspectives on imitation : from neuroscience to social science. - Hurley, S. L. (Susan L.); Chater, Nick (Perspectives on imitation: from neuroscience to social science, 2005)
A state-of-the-art view of imitation from leading researchers in neuroscience and brain imaging, animal and developmental psychology, primatology, ethology, philosophy, anthropology, media studies, economics, sociology, education, and law. Leading researchers across a range of disciplines provide a state-of-the-art view of imitation, integrating the latest findings and theories with reviews of seminal work, and revealing why imitation is a topic of such intense current scientific interest.